Electrostatic interactions modulate the RNA-binding and transactivation specificities of the human immunodeficiency virus and simian immunodeficiency virus Tat proteins. - Tao, J (1993)
The transcriptional activating (Tat) proteins from human immunodeficiency virus and simian immunodeficiency virus are sequence-specific RNA-binding proteins. In human immunodeficiency virus Tat, a single arginine residue, flanked on each side by three to four basic amino acids, mediates specific binding to a bulge region in trans-acting responsive element (TAR) RNA. We have systematically mutated the flanking charged residues and found that, in addition to the position of the sequence-specific arginine, the particular arrangement of nonspecific electrostatic interactions is an important determinant of RNA-binding specificity and transactivation activity. These additional electrostatic contacts may help stabilize the structure of TAR RNA when bound to arginine. One critical electrostatic interaction, located two residues N-terminal to the arginine, is absent in the simian immunodeficiency virus Tat protein and accounts for the difference in promoter specificities of the human and simian immunodeficiency viral proteins.